On some nonlinear fractional PDEs in physics - Ahmad, Jamshad; Mohyud-Din, Syed Tauseef (BIBECHANA, 2014)
In this paper, we applied relatively new fractional complex transform (FCT) to convert the given fractional partial differential equations (FPDEs) into corresponding partial differential equations (PDEs) and Variational Iteration Method (VIM) is to find approximate solution of time- fractional Fornberg-Whitham and time-fractional Wu-Zhang equations. The results so obtained are re-stated by making use of inverse transformation which yields it in terms of original variables. It is observed that the proposed algorithm is highly efficient and appropriate for fractional PDEs arising in mathematical physics and hence can be extended to other problems of diversified nonlinear nature. Numerical results coupled with graphical representations explicitly reveal the complete reliability and efficiency of the proposed algorithm. DOI: http://dx.doi.org/10.3126/bibechana.v12i0.11687 BIBECHANA 12 (2015) 59-69